Subprodutos da agroindústria atuam como fonte de carbono e alimento no cultivo do camarão Litopenaeus vannamei - Leite, Jordana Sampaio (2020)
The objective of this study was to evaluate the use of vegetable by-products as a source of carbon and food for the heterotrophic cultivation of juvenile shrimp L. vannamei. The first chapter evaluated or the effect of fertilizers prepared with by-products from rice processing on water quality and zootechnical parameters in the cultivation of L. vannamei juveniles. Shrimp of 0.98 ± 0.10 g were reared in 49 tanks of 1.5 m3 for 77 days under 127 animals/m2 . Rice bran, rice grits, and rice hulls were to form five different fertilizers with varying fiber content (F90, F110, F150, F200 and F250 g/Kg). They were compared to sugarcane molasses (MO) and unfertilized tanks (UNF), and applied in water three times a week at a fixed rate of 4.5 g/m3 . Settleable solids (SS) were higher in tanks fertilized with rice by-products (from 2.5 ± 1.0 to 3.1 ± 1.1 mL/L) and MO (3.4 ± 1.0 mL/L). Total ammonia nitrogen (0.19 ± 0.09 mg/L) and nitrite (5.97 ± 2.04 mg/L) no differences between treatments. However, all tanks treated with rice by-products, except 90 g/kg of fiber, resulted in a higher final shrimp body weight (from 9.04 ± 1.56 to 9.52 ± 1.89 g) compared to MO (8.75 ± 2.14 g) and UNF (7.74 ± 1.48 g). It can be concluded that a mixture of rice by-products is equally or more effective as a carbon source for the culture of L. vannamei compared to MO. The second chapter compared the use of unfermented rice processing residues and fermented residues, supplemented with the yeast S. cerevisiae (s) in the cultivation of L. vannamei shrimp. Shrimp of 0.95 ± 0.10 g were stocked in 49 tanks of 1 m3 under 127 animals/m2 and grown for 70 days. Shrimp grown under F90f and F110fs reached the highest final body weight (11.65 ± 0.93 and 11.75 ± 1.33 g, respectively). The use of fermented by-products from rice processing, supplemented with yeast, is more advantageous than the same unfermented residues in the intensive culture of L. vannamei. The third chapter evaluated the effect of different replacement levels of a practical feed for grain-based pellets (0, 25, 50, 75 and 100%) that underwent fermentation. Shrimp of 1.15 ± 0.12 g were stocked in 35 tanks of 1.0 m3 under 133 animals/m2 After 77 days, final shrimp survival reached 89.3 ± 5.7%, unaffected by the percentage of feed replacement (P>0.05). Final body weight (12.64 ± 2.54 and 11.71 ± 1.86 g), weekly growth (1.06 ± 0.14 and 0.97 ± 0.06 g/week), yield (1,365 ± 148 and 1,290 ± 87 g/m2 ) and the FCRt (1.32 ± 0.11 and 1.63 ± 0.07) did not differ between 0 and 25%, respectively. The present study indicated that it is possible to replace a proportion of up to 25% with grain pellets in the cultivation of L. vannamei in high youth density.